Peran Asosiasi Pengusaha Indonesia (APINDO) Memanfaatkan kebijakan Sistem Informasi Pasar Kerja (SIPK) 2024 - Imron Natsir (Lembaga Pengembangan Kinerja Dosen, 2024)
The Indonesian Employers Association (APINDO) plays a crucial role in addressing the gap between workforce supply and industrial demand. This study explores how APINDO leverages the Labor Market Information System (SIPK) to align human resources with industry needs, thereby enhancing employment rates and improving the efficiency of the labor market. The SIPK provides comprehensive data on labor market trends, job vacancies, and skill requirements, enabling employers to make informed decisions about hiring and training. Through interviews with key stakeholders and analysis of SIPK data, this research highlights the effectiveness of APINDO's strategies in optimizing human resource absorption. The findings indicate that APINDO's utilization of SIPK not only bridges the gap between job seekers and employers but also contributes to the development of a more responsive and adaptive workforce, meeting the evolving needs of industries in Indonesia. The study concludes with recommendations for enhancing the SIPK platform and expanding APINDO's initiatives to further support the alignment of labor supply and demand.